PENGARUH KESIAPAN BELAJAR TERHADAP KEDISIPLINAN PESERTA DIDIK KELAS 8 PADA MATA PELAJARAN PAI DI SMP RIFA’IYAH 01 SAPURAN - Arifin, Yusup; Khoiri, Ahmad; Vava Imam Agus Faisal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) determine the level of students’ learning readiness, (2) determine the level of students’ discipline, and (3) examine the effect of learning readiness on students’ discipline in Islamic Religious Education at SMP Rifa’iyah 01 Sapuran. This study used a quantitative approach with a correlational research design. Data were collected through questionnaires and documentation. The data were analyzed using validity test, reliability test, normality test, Product Moment correlation, simple linear regression, and t-test with the help of SPSS. The results show that students’ learning readiness is in the good category with an average score of 29, while students’ discipline is also in the good category with an average score of 25.5. The correlation analysis indicates a very strong relationship between learning readiness and discipline, with a correlation coefficient of 0.980 and a significance value of 0.000. In addition, learning readiness contributes 96.1% to students’ discipline. It can be concluded that learning readiness has a significant effect on students’ discipline. The better the students’ learning readiness, the higher their level of discipline in the learning process.